The generic classification of the Trochilini (Aves: Trochilidae): Reconciling taxonomy with phylogeny - Stiles, F. Gary; Remsen, J. V. Jr.; Mcguire, Jimmy A. (Zootaxa, 2017)
The generic nomenclature of the hummingbirds is unusually complicated. McGuire et al.’s (2014) recent phylogeny of the Trochilidae based on DNA sequence data has greatly clarified relationships within the family but conflicts strongly with the traditional classification of the family at the genus level, especially that of the largest and most recently derived clade, the Trochilini or “emeralds”. We recently presented a historical review of this classification and the generic modifications required by the Code of the International Commission on Zoological Nomenclature. Herein we present a revised generic classification of the Trochilini based upon McGuire et al.’s genetic data, while producing diagnosable generic groupings and preserving nomenclatural stability insofar as possible. However, this generic rearrangement has necessitated the resurrection of nine generic names currently considered synonyms, the synonymization of seven currently recognized genera and the creation of one new genus. The generic changes we recommend to the classification are drastic, and we summarize these in tabular form in comparison with the three most recent classifications of the Trochilini. Where appropriate, we outline alternatives to our proposed arrangement. The classification treats 110 species in 35 genera, including two species that remain unplaced for lack of genetic samples.